(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Chronic kidney disease (CKD) is a progressive disorder leading to impaired renal function, often complicated by thyroid dysfunction. Diabetes is a major contributor to CKD and may exacerbate thyroid abnormalities, which include subclinical hypothyroidism, overt hypothyroidism, and subclinical hyperthyroidism. Thyroid dysfunction in CKD patients can worsen clinical outcomes, highlighting the need for early detection and management. Aim & Objective: To compare thyroid profiles in diabetic and non-diabetic CKD patients and assess the prevalence and distribution of thyroid dysfunction across genders and CKD stages. Materials & Methods: An observational, comparative study was conducted at I.G. ESIC Hospital, Delhi, including 90 patients (>18 years) divided equally into diabetic and non-diabetic CKD groups. Blood samples were analyzed for Free T3, Free T4, and TSH using ELISA. Patients with known thyroid disorders, severe trauma, liver disease, nephrotic syndrome, or medications affecting thyroid function were excluded. Data were analyzed using SPSS, with significance set at p<0.05. Results: Thyroid dysfunction was more prevalent in diabetic CKD patients and females across both groups. Subclinical hypothyroidism was the most common abnormality, followed by overt hypothyroidism and subclinical hyperthyroidism. Euthyroid status was more frequent in males and non-diabetic CKD patients. Thyroid dysfunction increased with CKD severity, peaking in Stage 5, with diabetic patients consistently showing higher prevalence than non-diabetics. Conclusion: Thyroid dysfunction is common in CKD, particularly among diabetic patients and females, and correlates with disease severity. Routine thyroid screening and early management are recommended to improve outcomes in CKD patients.